2022
DOI: 10.32479/ijefi.13664
|View full text |Cite
|
Sign up to set email alerts
|

Does Foreign Aid Have an Expected Role in the Economic Growth of Bangladesh? An Analysis in ARDL Approach

Abstract: Bangladesh, a lower-middle-income country in South Asia and expected to be a developing country by 2024, is one of the most densely populated countries in the world, with 166.30 million (WDI, 2021) people. Foreign Aid (FA) plays a vital role in the economic development of Bangladesh. Foreign Aid, loans, and grants generally, which we call Official Development Assistance (ODA) (in this study, we have used the term 'Foreign aid') have increased gradually over the years after the liberation of Bangladesh with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…This is particularly true if the recipient country executes proper policies. Also, other scholars such as Ewubare & Ozigbu (2019) and Nderitu & Wenani (2023) argued that foreign aid has both positive and negative impact on the economic growth and economic development of the third world countries (Fasanya & Onakoya, 2022). It is based on this that the paper aims to investigate the impact of foreign aids on human capital development in Nigeria with a view to closing the precarious gap that exists between foreign aids and human capital development in Nigeria.…”
Section: Statement Of the Problemmentioning
confidence: 98%
See 1 more Smart Citation
“…This is particularly true if the recipient country executes proper policies. Also, other scholars such as Ewubare & Ozigbu (2019) and Nderitu & Wenani (2023) argued that foreign aid has both positive and negative impact on the economic growth and economic development of the third world countries (Fasanya & Onakoya, 2022). It is based on this that the paper aims to investigate the impact of foreign aids on human capital development in Nigeria with a view to closing the precarious gap that exists between foreign aids and human capital development in Nigeria.…”
Section: Statement Of the Problemmentioning
confidence: 98%
“…The impact of foreign aids is debatable among development economists. Some are of the opinion that external aid has no positive impact on economic growth, let alone economic development (for example, Boone, 1996 in Fasanya & Onakoya, 2022). Others such as Burnside and Dollar (2000) as cited in Fasanya & Onakoya (2022) hold a strong belief that foreign aids contributes significantly in improving economic development of less developed countries like Nigeria.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Tüzemen and Tüzemen (2015) also suggested a negative relationship between ODA and economic growth in Turkey. Other researchers, such as (Moreira, 2005;Fasanya &Onakoya, 2012 andSiddique, Kian, &Batool2018), found that ODA improved economic growth.…”
Section: Introductionmentioning
confidence: 95%
“…The findings revealed a negative influence of foreign aid on economic growth. Fasanya and Onakoya (2012) examined the impact of ODA on Nigerian economic growth from 1970 -2010 using the neoclassical modelling analytical framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sakyi (2011) found foreign aid and trade openness significantly and positively influenced economic growth. Fasanya and Onakoya (2012) study on the effect of ODA on economic expansion in Africa concluded that the inflow of aid into the nation promoted economic growth by boosting domestic savings and investments, freeing up resources that improve domestic investment. Fayissa and El-Kaissy (1999) concluded that because international aid supplements domestic savings rather than substituting for them, it has a positive impact on the growth of the economies of developing states.…”
Section: Literature Reviewmentioning
confidence: 99%